Data science from scratch Zhong wen ban yong Python xue zi liao ke xue = Data science from scratch / = Data science from scratch - Grus, Joel (GoTop Information, Inc., 2016)
Detailed summary in vernacular field.
Non-Latin script record. - Includes index
Keywords: Python (Computer program language); Data mining; Data mining -- Mathematics; Data structures (Computer science); Python (Langage de programmation); Exploration de données (Informatique); Exploration de données (Informatique); Mathématiques; Structures de données (Informatique); Data mining; Mathematics